BNO 1095, a Standardized Dry Extract from the Fruits of Vitex agnus-castus, Impairs Angiogenesis-related Endothelial Cell Functions In Vitro - Bischoff-Kont, Iris; Brabenec, Laura; Ingelfinger, Rebecca; Nausch, Bernhard; Fürst, Robert (Planta Medica, 2021)
BNO 1095, a standardized dry extract from the fruits of Vitex agnus-castus, represents an approved herbal medicinal product for the treatment of premenstrual syndrome. Angiogenesis, the formation of new blood vessels from pre-existing capillaries, plays a major role in physiological situations, such as wound healing or tissue growth in female reproductive organs, but it is also of great importance in pathophysiological conditions such as chronic inflammatory diseases or cancer. Angiogenesis is a highly regulated multi-step process consisting of distinct key events that can be influenced pharmacologically. Few studies suggested anti-angiogenic actions of V. agnus-castus fruit extracts in in vivo and ex vivo models. Here, we provide for the first time profound in vitro data on BNO 1095-derived anti-angiogenic effects focusing on distinct angiogenesis-related endothelial cell functions that are inevitable for the process of new blood vessel formation. We found that V. agnus-castus extract significantly attenuated undirected and chemotactic migration of primary human endothelial cells. Moreover, the extract efficiently inhibited endothelial cell proliferation and reduced the formation of tube-like structures on Matrigel. Of note, the treatment of endothelial cell spheroids almost blocked endothelial sprouting in a 3D collagen gel. Our data present new and detailed insights into the anti-angiogenic actions of BNO 1095 and, therefore, suggest a novel scope of potential therapeutic applications of the extract for which these anti-angiogenic properties are required.
Keywords: Vitex agnus-castus; Lamiaceae; endothelial cells; angiogenesis-related cell functions